Integration of decentralized torrefaction with centralized catalytic pyrolysis to produce green aromatics from coffee grounds. (February 2016) - Chai, Li; Saffron, Christopher M.; Yang, Yi; Zhang, Zhongyu; Munro, Robert W.; Kriegel, Robert M.
Highlights: BTEX costs can be reduced using biomass pre-processing methods such as torrefaction. Long distance biomass supply is benefitted when using torrefaction to pre-process biomass. When biomass cost exceeds 58/tonne, the mass loss that occurs during torrefaction negates its benefit. Abstract: The aim of this work was to integrate decentralized torrefaction with centralized catalytic pyrolysis to convert coffee grounds into the green aromatic precursors of terephthalic acid, namely benzene, toluene, ethylbenzene, and xylenes (BTEX). An economic analysis of this bioproduct system was conducted to examine BTEX yields, biomass costs and their sensitivities. Model predictions were verified experimentally using pyrolysis GC/MS to quantify BTEX yields for raw and torrefied biomass. The production cost was minimized when the torrefier temperature and residence time were 239 °C and 34 min, respectively. This optimization study found conditions that justify torrefaction as a pretreatment for making BTEX, provided that starting feedstock costs are below 58 per tonne.